Outcome of Fetus and Mother in Covid-19 Positive Pregnancies: A Retrospective Study - Pari Gul Baloch, Erum Ilyas, Shazia Ramzan, Pinkey Kumari, Paras Mangi, Sabita Devi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim:To assess the Feto-Maternal Outcome in Covid-19 Positive Pregnancies Study design: A retrospective study Place and duration: This study was conducted at Sheikh khalifa bin Zayed hospital Quetta, Pakistan from February 2020 to Feburary2021 Methodology:After ethical committee approval for the study, all medical records were evaluated for symptomatic and asymptomatic COVID-19 positive pregnant females. After admission to the hospital, an experienced healthcare worker validated the SARS-COV-2 status of all afflicted women by taking nasopharyngeal swabs for real-time RT-PCR following WHO criteria.Bothfeto-maternal outcomes were observed, including psychological stress, fever, cough, sore throat, dyspnea, ICU hospitalizations, pneumonia, maternal transfer of COVID to newborn. SPSS version 22 was used to analyze the data. Results:The present study investigated 72 COVID-19 positive pregnant women. The mean age of females was 28 ± 5.6 years, and the mean gestational age was 37 weeks. The common symptoms were anxiety (18.1%), runny nose with fever (12.5%), cough and fever (9.7%), and sore throat (8.3), whereas 48.6% of cases were asymptomatic. Co-Morbidities include Hypertension (19.7), Anemia (8.3%), Diabetes Mellitus (5.6%), and Hypothyroidism (2.8%). Conclusion: The clinical course of COVID-19 infection in pregnant women appears similar to that of non-pregnant women. There was no vertical transmission of COVID-19, nor was there any neonatal mortality.